Lactococcus lactis strain Plasma activates plasmacytoid dendritic cells and mitigates common cold-like symptoms in healthy adults: a meta-analysis of individual participant data - Kato, Yukiko; Kobayashi, Keiko; Kuramochi, Yui; Miyata, Toshio; Ushida, Yusuke; Hayamizu, Kohsuke (Frontiers in Immunology, 2025)
BackgroundPlasmacytoid dendritic cells (pDCs) are a type of immune cell that play a crucial role in the defense against viral infection. Multiple randomized controlled trials (RCTs) have reported that oral intake of Lactococcus lactis strain Plasma (LC-Plasma) activates pDCs and reduces cold-like symptoms. This study conducted a meta-analysis to comprehensively evaluate the effects of oral LC-Plasma intake on pDC activation and cold-like symptoms by comparing healthy adults.MethodThis study targeted RCTs that examined the effects of oral intake of LC-Plasma or placebo food products on pDC activation or common cold-like symptoms in healthy adult males and females. Data sources included PubMed, Cochrane Library, J-Dream III, UMIN-CTR, and the International Clinical Trials Registry Platform, with searches conducted up to June 21st, 2024. The primary outcome evaluated pDC activation, and the secondary outcome evaluated the subjective evaluation of common cold-like symptoms. A quantitative synthesis was performed by meta-analysis using random-effects models. Two authors independently assessed risk of bias using the revised Cochrane risk of bias tool (RoB2).ResultsAmong the eight RCTs that met the eligibility criteria for this study, individual participant data (IPD) were obtained from seven. Since we were unable to obtain IPD from the remaining study, we integrated data from this study based on its final report. The meta-analysis in this study, conducted using data from 619 participants, revealed that the expression levels of pDC activation markers, CD86 and HLA-DR, were significantly maintained during LC-Plasma intake when compared to the placebo control group (CD86: SMD = 0.37, 95% CI (confidence interval): 0.17 to 0.57; HLA-DR: SMD = 0.47, 95% CI: 0.21 to 0.73). In addition, LC-Plasma intake significantly reduced the cumulative number of days per 28 days of cough and feverishness compared to the control group, according to the meta-analysis using data from 555 participants (Cough: MD=-0.69, 95%CI: -1.24 to -0.14; Feverishness: MD=-0.26, 95%CI: -0.52 to -0.0038).ConclusionThis study is the first to present, through integrated analyses using identical analytical conditions, that daily intake of LC-Plasma may help sustain pDC activation and could be useful in reducing cough and feverishness, typical cold-like symptoms.Systematic Review Registrationhttps://www.umin.ac.jp/, identifier UMIN000054706.